Association between sleep duration and hypertension of migrant workers in China: a national cross-sectional surveillance study - Xiao Zhang; Chun Li; Yunqi Guan; Mei Zhang; Zhenping Zhao; Zhengjing Huang; Qian Xiao; Limin Wang (BMJ Open)
Objectives To examine the relationship between sleep duration and hypertension of migrant workers aged 18–59 years in China.Design Population-based cross-sectional study using a complex survey sampling design.Participants There were 43 655 subjects in our analysis, after excluding people with missing information for key exposure and outcome variables and abnormal values for sleep duration (≤2 or ≥17 hours).Primary outcome measure Hypertension was defined as systolic blood pressure (BP) ≥140 mm Hg and/or diastolic BP ≥90 mm Hg, or self-reported history of hypertension diagnosis in hospitals at the township (community) level or above and use of hypertensive medicine in the last 2 weeks.Results Of 43 655 subjects, 15.6% (95% CI 15.1% to 16.1%) of migrant workers had hypertension. The prevalence of hypertension decreased with the increased sleep duration, both in males and females. Logistic regression models, using 7–8 hours sleep/day as the reference, showed a greater odds for hypertension among men and women who reported <6 hours of sleep after adjusting for sociodemographic characteristics, behavioural risk factors, body mass index, diabetes, stroke and myocardial infarction (men: OR 1.26; 95% CI 1.03 to 1.54, women: OR 1.55; 95% CI 1.13 to 2.06, pinteraction=0.096). Further stratified by age and migration time, it revealed that among adults less than 45 years old, those sleeping 9 or more hours had adjusted odds for hypertension of 0.82 (95% CI 0.72 to 0.93, pinteraction=0.020),while there was no evidence of an association between sleep duration and hypertension among adults aged 45–59 years. Among adults whose migration time was less than 4.5 years, those sleeping 9 or more hours had adjusted odds for hypertension of 0.80 (95% CI 0.68 to 0.94, pinteraction=0.097).Conclusion The association between sleep duration and hypertension varies by age. Short sleep duration (<6 hours) is associated with an increased prevalence of hypertension in both genders.